New Economic Politics and Institutional Approach for the Nation Problem - Adam, A.; Rahayu, Sri; Muhajir, Ahmad; Widayat, Edy; Ismail; Sumartono (International Journal of Psychosocial Rehabilitation, 2020)
Indonesia is a rich nation in normal assets, however destitution, joblessness, financial and instructive abberations despite everything portray the life of the country and state. The nearness of the state to make fair thriving for all individuals or society inside the structure of the unitary condition of the Republic of Indonesia has not yet been figured it out. The job of the administration and financial entertainers will decide the acknowledgment of the nation’s standards to make a prosperous society in balance and manageable way. Government with its capacity can manage, regulate, and give concentrated so financial entertainers can assume an ideal job for their inclinations without disregarding their obligations to the administration and society. Financial on-screen characters, through their innovative conduct that make monetary worth included that is a wellspring of abundance of a country state. Main concern: business people make riches for the country.